Influence of Media in the Choice of Oral Hygiene Products Used Among the Population of Maduravoyal, Chennai, India - Anitha Logaranjani; Jaideep Mahendra; Rajapriya Perumalsamy; Rajeshree Rangari Narayan; Sathish Rajendran; Ambalavanan Namasivaya (Journal of Clinical and Diagnostic Research, 2015)
Background and Aims: To assess the factors influencing the awareness and practice of oral hygiene among the local population Maduravoyal, Chennai, India. Materials and Methods: A cross-sectional questionnaire based study was conducted to understand the factors influencing the choice and practice of oral hygiene products among the population of Maduravoyal, Chennai, India. Data was collected by means of a self administered structured questionnaire written in English and validated through a pilot survey. One thousand two hundred and nine subjects, with an age range of 15 to 70 years, who visited the Department of Periodontology, Meenakshi Ammal Dental College, Chennai were selected for investigation. The data obtained was analyzed using the SPSS version 13.0. The frequency of distribution and percentages were calculated. Results: The results of the study showed that tooth brush (98.5%) and toothpaste (98%) were the main products used for the maintenance of oral hygiene and around 84.6% of the population brushed once daily. Information from the media (59.4%) and decay prevention (49.7%) were the major factors that influenced the choice of toothpaste among the study population. Conclusion: The major factor which influenced the choice of oral hygiene products was based on information obtained from advertisements and other sources. There is a need for the dental professionals to be aware of the ever-increasing development and marketing of oral hygiene products from various databases. Hence, the education of people regarding the importance of oral hygiene maintenance, proper selection of oral hygiene products is essential.